2011
DOI: 10.1007/s00421-011-1995-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic loading of sodium bicarbonate in highly trained swimmers

Abstract: In the present study, 200-m swim time in highly trained male swimmers was measured on two consecutive days (Trial 1 and Trial 2) and under three conditions [(1) acute loading, AcL; (2) chronic loading, ChL; (3) Placebo, PLA]. No sodium bicarbonate (NaHCO(3)) was administered between Trial 1 and Trial 2 under each condition. Blood lactate concentration ([La(-)]), base excess of extracellular fluid (BE(ecf)), plasma bicarbonate concentration ([HCO(3) (-)]) and pH were determined before and after capsule administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 22 publications
3
35
0
5
Order By: Relevance
“…Joyce et al (2012) found no improvement in 200-m swim time after bicarbonate treatment. Some of the variation in the reported effects of bicarbonate administration is undoubtedly a result of the nature of the task, but a recent meta-analysis also found that effects are less likely to be observed in well-trained athletes than in recreationally active individuals (Peart et al, 2012).…”
Section: Bicarbonate and Beta-alaninementioning
confidence: 84%
“…Joyce et al (2012) found no improvement in 200-m swim time after bicarbonate treatment. Some of the variation in the reported effects of bicarbonate administration is undoubtedly a result of the nature of the task, but a recent meta-analysis also found that effects are less likely to be observed in well-trained athletes than in recreationally active individuals (Peart et al, 2012).…”
Section: Bicarbonate and Beta-alaninementioning
confidence: 84%
“…Some studies have examined the ergogenic potential of SB on short-distance swimming performance (i.e., 100 and 200 m or 100 and 200 yards) and interval swimming performance (Gao et al 1988;Pierce et al 1992;Lindh et al 2008;Pruscino et al 2008;Siegler and Hirscher 2010;Joyce et al 2012). However, results are quite conflicting; some studies reported no effect of SB on timetrial performance (Pierce et al 1992;Pruscino et al 2008;Joyce et al 2012), one reported a positive effect on swimming trials (Lindh et al 2008), and others reported improved interval swimming performance (Gao et al 1988;Siegler and Hirscher 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, results are quite conflicting; some studies reported no effect of SB on timetrial performance (Pierce et al 1992;Pruscino et al 2008;Joyce et al 2012), one reported a positive effect on swimming trials (Lindh et al 2008), and others reported improved interval swimming performance (Gao et al 1988;Siegler and Hirscher 2010). However, no study has yet investigated the effects of BA supplementation on swimming performance.…”
Section: Introductionmentioning
confidence: 99%
“…Despite greater muscular pain and increased creatine kinase levels on day 2 after caffeine use, performance was improved by 5.0 [±3.6] % and 5.1 [±2.8] %Beetroot juice/nitrate Hoon et al [57]Highly-trained cyclists ( n  = 26 M) Crossover design70-ml (4 mmol nitrate) BJ concentrate @ 2.5 h pre TT1 or @ 2.5 h pre TT2 or 70 ml BJ @ 2.5 pre TT1 + 35 ml BJ top up straight after TT1Cycling 2 × 4 min cycling TT separated by 75 min (simulation of team pursuit schedule at London Olympic Games)Event 1: PerhapsEvent 2: Potential impairmentSophisticated mixed model analysis took into account caliber of cyclist and learning/order effect, while identifying 1% improvement as the smallest worthwhile change. Overall, nitrate treatment (acknowledged as a suboptimal dose in light of more recent evidence) was associated with a small but unclear improvement of 1.3 ± 1.7% in the first time trial, but also a potentially unclear impairment of performance in the second time trial, perhaps due to the carryover of additional fatigue [−0.3 ± 1.6%]Bicarbonate Joyce et al [58]Highly-trained swimmers ( n  = 8 M) Crossover designSerial bicarbonate protocol: 3 days @ 300 mg/kg/day sodium bicarbonate divided in 3 daily doses + final dose on day 4Performance protocol undertaken on days 4 and 5Swimming 2 × 200 m TT separated by 24 h to simulate swimming competitionEvent 1: NoEvent 2: NoPlasma bicarbonate concentration was increased after 3 days’ serial loading, although to a smaller extent than when same daily amount was taken as acute dose 90 min before the TT. However bicarbonate concentrations returned to baseline 24 h after last dose.…”
Section: Repeated Use Of Supplementsmentioning
confidence: 99%
“…Finally, repeated use of bicarbonate supplementation has been studied in several sports-specific study designs, simulating a successive day use in a swimming carnival [58] or repeated use in a rowing regatta where races may be separated by 48 h [37]. Both studies (see Table 4) used the serial bicarbonate loading protocol in which 300–500 mg/kg of bicarbonate is taken daily in split doses to chronically elevate plasma bicarbonate concentrations [9].…”
Section: Repeated Use Of Supplementsmentioning
confidence: 99%